Estética e Sociabilidade: o problema da religião no jovem Hegel (Revista Eletrônica Estudos Hegelianos, 2020)
The main objective of this paper lies in assessing the relation of sensibility and imagination in comprising an aesthetical project for ethics and politics. It aims at establishing how sensibility and imagination are thought as primordial ethical powers. This will be accomplished by analyzing the role religion plays in young Hegel’s writings and in which way Hellenism constitutes a counterbalance to his Enlightenment inheritance. Texts and fragments dated up to Bern’s period will be analyzed in order to integrate these writings into a cohesive theoretical framework and therefore offer a wider and clearer picture of how three general guidelines lead Hegel’s reflections: the sensible-intelligible duality problematic, the adherence to an Hellenic ideal of unity, and the reframing of primal Enlightenment motifs, especially those formulated by Rousseau and Kant. These three main flows form the basis upon which I analyze how the categories of positivity, autonomy and reason are called upon and reframed by the young Hegel in the shaping of the concepts of his Republican ideal, namely subjective religion and folk religion. The intended result comprises of proving that the young Hegel’s concern revolves around the ethical and social limits of the private-public duality, and his solution is to resort to a kind of simple experience of life led by the Greeks and which could change Modern social relations through their religious beliefs and practices into more reconciliatory forms of life between individuum and community.